'Happy Meals': Finding Happiness with Hans Becker and the Humanitas Care Model. (March 2014) - Birkbeck, David; Farrelly, Lorraine
Abstract Hans Becker, originally a professor at the Erasmus School of Economics in Rotterdam, is a seemingly unlikely guru for elderly care. In 1992 he was appointed Chair of the Rotterdam‐based housing association Humanitas with the task of overturning the outmoded and failing commercial model of its nursing homes. He set about replacing them with 'apartments for life' that promoted independent living. In order to understand more about the successful Humanitas model, David Birkbeck, Chief Executive of Design for Homes in the UK, interviewed Becker and found out how the move to a new housing type was enabled by a philosophical shift that placed an emphasis on the engendering of happiness among its residents – with food and the creation of convivial on‐site restaurant facilities proving a critical tool.